2019
DOI: 10.1186/s12967-019-2023-z
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A8 can serve as potential prognostic biomarker and therapeutic target for ovarian cancer: based on the comprehensive analysis of Annexins

Abstract: Background Annexins are involved in vesicle trafficking, cell proliferation and apoptosis, but their functional mechanisms in ovarian cancer remain unclear. In this study, we analyzed Annexins in ovarian cancer using different databases and selected Annexin A8 (ANXA8), which showed the greatest prognostic value, for subsequent validation in immunohistochemical (IHC) assays. Methods The mRNA expression levels, genetic variations, prognostic values and gene–gene interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 57 publications
0
34
1
Order By: Relevance
“…We utilized TISIDB ( ) to explore the relationship between the expression of genes and infiltration of tumor-infiltrating immune cells, including CD4 + T cells, CD8 + T cells, B cells, neutrophils, monocytes, eosinophils, mast cells, DCs, NKT cells, NK cells, MDSCs, and CD56 cells ( 27 , 28 ). TISIDB is an online tool that includes genomic, transcriptomic and clinical data for 30 cancer types from the TCGA database.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized TISIDB ( ) to explore the relationship between the expression of genes and infiltration of tumor-infiltrating immune cells, including CD4 + T cells, CD8 + T cells, B cells, neutrophils, monocytes, eosinophils, mast cells, DCs, NKT cells, NK cells, MDSCs, and CD56 cells ( 27 , 28 ). TISIDB is an online tool that includes genomic, transcriptomic and clinical data for 30 cancer types from the TCGA database.…”
Section: Methodsmentioning
confidence: 99%
“…To further investigate the association between VISTA and cancer immunity, we utilized the Tumor and Immune System Interaction Database (TISIDB, http://cis. hku.hk/TISIDB) [44,53] to analyze the potential relevance of VISTA in multiple immune regulatory cells and molecules across 30 cancer types. In accordance with previous reports about the contradictory roles of VISTA in cancer immunity, the outcomes of integrated immunological correlation analyses showed the following: (1) VISTA expression levels correlated positively with the relative abundance of almost all types of TILs with tumor-suppressing or tumor-promoting functions across 30 types of cancers, including but not limited to, activated CD8 T cells, natural killer cells, regulatory T cells, and MDSC ( Fig.…”
Section: Expression Profile Of Vistamentioning
confidence: 99%
“…Of note, ANXA8 is crucial in the maintenance of the late endosomal/lysosomal compartment physiological functions in cancer cells [16] and is able to interact with phosphatidylinositides and actin-associated membrane domains [25] which are closely related to cell migration, cytokinesis, vesicle transport and cellular immunity. It has also been clarified that high expression of ANXA8 in pancreatic cancer [20][21][22] and ovarian cancer [23] was correlated with tumor cell invasion and proliferation. ANXA8 transcription is down-regulated by EGFR and its downstream targets, phosphatidylinositol-3-kinase and Akt, are universally known as key factors of tumors proliferation, migration and metastasis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ANXA8 has also been linked to the formation of endosomes and epidermal growth factor receptor (EGFR) turnover in Hela cells [16]. Other reports demonstrated that the expression of ANXA8 is significantly increased in breast cancer [17][18][19], pancreatic cancer [20][21][22], ovarian cancer [23] and cholangiocarcinoma [24]. Thus, ANXA8 is expected to be a new biomarker and molecular therapeutic target for the diagnosis, treatments and prognosis of multiple diseases, especially malignant tumors.…”
Section: Ivyspring International Publishermentioning
confidence: 99%